2020
DOI: 10.1108/jmh-09-2018-0050
|View full text |Cite
|
Sign up to set email alerts
|

Leadership lessons from the Titanic and Concordia disasters

Abstract: Purpose This paper aims to investigate two famous disasters at sea, the Titanic and the Concordia, separated by 100 years, based on a comparison and analysis of those historical events, demonstrating how lessons learned and training methods used in the hazardous marine environments of aircraft carrier operations, as well as the near-solo conditions of technical scuba diving, can be better implemented in managing a large ship at sea. Design/methodology/approach This study starts with a historical analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…There are many cases in the literature of leaders and organizations applying principles from other contexts to manage crises. While not a divergent as using performing skills in comedy to manage an invasion, Marko et al (2020) showed how planning and split-second decision-making strategies used for naval vessels and scuba diving can be used to train ships to respond to an unforeseen disaster at sea, using the Titanic as an historical illustration.…”
Section: Case 2: Leadership and Crisesmentioning
confidence: 99%
“…There are many cases in the literature of leaders and organizations applying principles from other contexts to manage crises. While not a divergent as using performing skills in comedy to manage an invasion, Marko et al (2020) showed how planning and split-second decision-making strategies used for naval vessels and scuba diving can be used to train ships to respond to an unforeseen disaster at sea, using the Titanic as an historical illustration.…”
Section: Case 2: Leadership and Crisesmentioning
confidence: 99%